Nucleation and growth kinetics of colloidal nanoparticles CdS:Mn in aqueous solution of polyvinyl alcohol - Rudko, G.Yu.; Fediv, V.I.; Savchuk, A.I.; Gule, E.G.; Vorona, I.P.; Nosenko, V.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
Colloidal undoped CdS and doped CdS:Mn nanoparticles were synthesized in
the solution of polyvinyl alcohol polymer, and the process of nanoparticles growth was
monitored by optical absorption measurements. The inclusion of Mn²⁺ impurity was
checked by electron paramagnetic resonance measurements. It is shown that the core of
CdS:Mn nanoparticle is undoped. The results obtained demonstrated that the rate of the
band gap value decrease during nanoparticles growth is slower for the Mn-doped
nanoparticles as compared to the undoped ones. This effect was ascribed to the inhibition
of nanoparticles growth in the solution containing manganese salt. The model of the
adsorptive doping of CdS NPs with manganese was proposed.